Transformative Music Learning Experiences: A Chinese Immigrant in Northeastern Brazil and his Love for Música Sertaneja (Per Musi, 2019)
This article uses the story of a Chinese immigrant in Brazil and his love of música sertaneja as a starting point to discuss his adaptation to a new society and the way in which his music learning played an important role in this process. Anchored in the ideals of Narrative Inquiry and inspired by Mezirow's Transformative Learning Theory, the article then extrapolates from this unique story to present a broad discussion that includes ideas about music education, immigration, identity, individual and social transformation, empowerment, and self-definition. The article concludes with reflections about the importance of music learning to the adaptation of immigrants in general, an idea that has wide applicability, being useful both for immigrants themselves, as well as for teachers and policymakers.